2012
DOI: 10.5047/eps.2012.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Field measurements and numerical modeling for the run-up heights and inundation distances of the 2011 Tohoku-oki tsunami at Sendai Plain, Japan

Abstract: We conducted an urgent field survey at the Sendai Plain to measure the run-up heights and inundation distances of the 2011 Tohoku-oki tsunami. We used GPS measurements because of the remarkably long inundation distances (ca. 5.4 km). We established an accurate measurement scheme using the far electric reference points (about 350 km). Using this method, we quickly measured 69 run-up heights within 3 days. The tsunami run-up heights and inundation distances varied mainly according to the local topography, rangin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…While in this study the two combined effects of shoaling and refraction are considered, there are phenomena associated with wave behavior that play a role in run-ups are not yet incorporated, including effects of reflection and dispersion, and energy dissipation. Other external parameters, such as the geometry of the coast, coastal topography, and nearshore bathymetry may influence run-up parameterization, as claimed by some previous work on run-up and inundation estimation (Hayashi, 2010;Mori et al, 2011;Chen et al, 2012;Goto et al, 2013;Lin et al, 2014). For now, this study does not consider these effects as it concerns only on a simple parameterization for tsunami run-up prediction and therefore the incorporation of more local effects into the run-up estimate is challenging for future work.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…While in this study the two combined effects of shoaling and refraction are considered, there are phenomena associated with wave behavior that play a role in run-ups are not yet incorporated, including effects of reflection and dispersion, and energy dissipation. Other external parameters, such as the geometry of the coast, coastal topography, and nearshore bathymetry may influence run-up parameterization, as claimed by some previous work on run-up and inundation estimation (Hayashi, 2010;Mori et al, 2011;Chen et al, 2012;Goto et al, 2013;Lin et al, 2014). For now, this study does not consider these effects as it concerns only on a simple parameterization for tsunami run-up prediction and therefore the incorporation of more local effects into the run-up estimate is challenging for future work.…”
Section: Resultsmentioning
confidence: 97%
“…(2). The calculated results are hereby compared to field data from observational studies available at http://www.ngdc.noaa.gov and direct surveys (Mori et al, 2011;Goto et al, 2013), and also to relevant data developed from numerical codes (Hirata et al, 2004;Lin et al, 2014). Detailed data and the calculated run-ups using Eq.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The susceptibility of a coastal area to geomorphological impacts from a tsunami mainly depend on coastal geomorphological and topographical factors that according to the literature have an effect on tsunami run-up, inundation depth and backwash dynamics that control the extent of the impacts [Dawson 1994, Matsutomi et al 2001, Choowong et al 2007, Goto et al 2011. Tsunami run-up and inundation dynamics vary significantly from site to site and studies have shown that the main controlling parameters are crustal deformation during the seismic event, orientation of propagation vector to the mean shoreline direction, distance from the tsunami generation area, bathymetry, coastal and land morphology [Geist 2001, Papathoma and Dominey-Howes 2003, Fritz et al 2011, Lekkas et al 2011.…”
Section: Tsunami Susceptibility Indicator (Tssi) Factorsmentioning
confidence: 99%